Acceleration of an Aromatic Claisen Rearrangement via a Designed Spiroligozyme Catalyst that Mimics the Ketosteroid Isomerase Catalytic Dyad - Parker, Matthew F. L. (American Chemical Society, 2014)
[Image: see text] A series of hydrogen-bonding catalysts have been designed for the aromatic Claisen rearrangement of a 1,1-dimethylallyl coumarin. These catalysts were designed as mimics of the two-point hydrogen-bonding interaction present in ketosteroid isomerase that has been proposed to stabilize a developing negative charge on the ether oxygen in the migration of the double bond.1 Two hydrogen bond donating groups, a phenol alcohol and a carboxylic acid, were grafted onto a conformationally restrained spirocyclic scaffold, and together they enhance the rate of the Claisen rearrangement by a factor of 58 over the background reaction. Theoretical calculations correctly predict the most active catalyst and suggest that both preorganization and favorable interactions with the transition state of the reaction are responsible for the observed rate enhancement.